(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article discusses the importance of Project-Based Learning (PBL) in Science, Technology, Engineering, Art, and Mathematics (STEAM) education. The authors argue that PBL, a student-driven approach that emphasizes hands-on, inquiry-based projects to solve real-world problems, promotes active and engaging learning, collaboration, community building, and the development of critical thinking, problem-solving, creativity, and communication skills. There is provided two examples of PBL in STEAM education, an artificial reef project, and a solar energy project, that highlight how PBL can be applied in different contexts to engage students in meaningful and practical learning experiences.